2006
DOI: 10.1074/jbc.m605858200
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Gene Encoding the Ubiquitously Expressed Glucose-6-phosphatase Catalytic Subunit-related Protein (UGRP)/Glucose-6-phosphatase Catalytic Subunit-β Results in Lowered Plasma Cholesterol and Elevated Glucagon

Abstract: In liver, glucose-6-phosphatase catalyzes the hydrolysis of glucose-6-phosphate (G6P) to glucose and inorganic phosphate, the final step in the gluconeogenic and glycogenolytic pathways. Mutations in the glucose-6-phosphatase catalytic subunit (G6Pase) give rise to glycogen storage disease (GSD) type 1a, which is characterized in part by hypoglycemia, growth retardation, hypertriglyceridemia, hypercholesterolemia, and hepatic glycogen accumulation. Recently, a novel G6Pase isoform was identified, designated UG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…G6P hydrolytic activity is decreased by ϳ50% in homogenates of G6pc3 Ϫ/Ϫ mouse brain and testis relative to wild-type tissue, consistent with the ability of G6PC3 to hydrolyze G6P (48). In addition, female, but not male, G6pc3 Ϫ/Ϫ mice exhibit growth retardation, as do G6pc Ϫ/Ϫ mice and patients with GSD type 1a (48). However, in contrast to G6pc Ϫ/Ϫ mice and patients with GSD type 1a, G6pc3 Ϫ/Ϫ mice exhibit no change in hepatic glycogen content or blood glucose or triglyceride levels.…”
Section: G6pc3mentioning
confidence: 71%
See 1 more Smart Citation
“…G6P hydrolytic activity is decreased by ϳ50% in homogenates of G6pc3 Ϫ/Ϫ mouse brain and testis relative to wild-type tissue, consistent with the ability of G6PC3 to hydrolyze G6P (48). In addition, female, but not male, G6pc3 Ϫ/Ϫ mice exhibit growth retardation, as do G6pc Ϫ/Ϫ mice and patients with GSD type 1a (48). However, in contrast to G6pc Ϫ/Ϫ mice and patients with GSD type 1a, G6pc3 Ϫ/Ϫ mice exhibit no change in hepatic glycogen content or blood glucose or triglyceride levels.…”
Section: G6pc3mentioning
confidence: 71%
“…Although G6pc3 Ϫ/Ϫ mice are not hypoglycemic, female G6pc3 Ϫ/Ϫ mice have elevated (ϳ60%) plasma glucagon and reduced (ϳ20%) plasma cholesterol. We hypothesize that the hyperglucagonemia prevents hypoglycemia and that the hypocholesterolemia is secondary to the hyperglucagonemia (48). As such, the phenotype of G6pc3 Ϫ/Ϫ mice is mild, indicating that G6PC is the major glucose-6-phosphatase of physiological importance for glucose homeostasis in vivo.…”
Section: G6pc3mentioning
confidence: 99%
“…À / À mice 21 were transduced with an ER-Hoxb8 retrovirus and cell lines were established. Cell lines from wt and G6PC3…”
Section: Resultsmentioning
confidence: 99%
“…The height and weight of the boy described by Arostegui et al 2 were below the third percentile and at least 7 of the 12 patients reported by Boztug et al 3 demonstrated growth retardation or height/weight at the lower end of the normal range. We note that female g6pc3 À/À mice exhibit growth retardation, 12 but in humans this features seems not to be sex limited.…”
Section: Growthmentioning
confidence: 99%